2017
DOI: 10.1371/journal.pone.0178690
|View full text |Cite
|
Sign up to set email alerts
|

Physician assessments of drug seeking behavior: A mixed methods study

Abstract: BackgroundPain complaints are common, but clinicians are increasingly concerned about overuse of opioid pain medications. This may lead patients with actual pain to be stigmatized as “drug-seeking,” or attempting to obtain medications they do not require medically. We assessed whether patient requests for specific opioid pain medication would lead physicians to classify them as drug-seeking and change management decisions.Methods and findingsMixed-methods analysis of interviews with 192 office-based primary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
(33 reference statements)
0
8
0
Order By: Relevance
“… USA Acute Physician Consultation style Ethnicity (black, white) Verbal and non-verbal communication between patient & physician Metastatic gastric and pancreatic cancer Physicians used similar verbal but different nonverbal communication behaviours with black and white patients. Fischer et al, 2017 [ 61 ] To test whether patient requests for specific opioid pain medication would lead physicians to classify them as drug-seeking and change management decisions USA Primary care Physician Prescription Ethnicity (black, white) Patient (drug seeking) behaviour Pain (sciatica) Physician suspicion of drug-seeking behaviour was much higher when patients requested opioid medication. Physician suspicion of drug-seeking behaviour did not vary by patient characteristics, including gender and race.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… USA Acute Physician Consultation style Ethnicity (black, white) Verbal and non-verbal communication between patient & physician Metastatic gastric and pancreatic cancer Physicians used similar verbal but different nonverbal communication behaviours with black and white patients. Fischer et al, 2017 [ 61 ] To test whether patient requests for specific opioid pain medication would lead physicians to classify them as drug-seeking and change management decisions USA Primary care Physician Prescription Ethnicity (black, white) Patient (drug seeking) behaviour Pain (sciatica) Physician suspicion of drug-seeking behaviour was much higher when patients requested opioid medication. Physician suspicion of drug-seeking behaviour did not vary by patient characteristics, including gender and race.…”
Section: Resultsmentioning
confidence: 99%
“…Six of the moderate and high quality studies sought to collect data in settings that replicated aspects of healthcare delivery, for example by collecting data in physicians’ offices during clinic times [ 61 , 66 , 68 ]. Such data collection was not always achieved as planned; Sheringham et al sought to conduct an online study in clinic settings between appointments, but due to limited clinic IT facilities many participants completed the study at home [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a recent editorial, Gorfinkel et al suggested that chronic pain patients may be misdiagnosed because the characteristics of mismanaged pain may mimic the criteria of opioid-use disorder 14. The need to understand clearly the reasons behind “liking” an opioid and the desire to “take it again” seem of paramount importance in patient populations 15…”
Section: Discussionmentioning
confidence: 99%
“…Seven articles elucidated the impact of a long-standing patient–provider relationship on prescribing opioids among a sample of 195 providers (166 primary care, 4 nurse practitioners, 8 physician assistants, 8 internal medicine, 3 specialists, 2 osteopath, 2 pharmacists, 2 other). 34 , 39 , 40 , 42 , 44 , 50 , 52 Having a long-standing relationship with a patient increased willingness to engage in discussions surrounding opioid prescribing. Providers noted that knowing the patient well, knowing their background, having a well-rounded level of trust, and having a strong relationship with their patient increased their comfort level when prescribing opioids: “If you’re the family doctor or long-term psychiatrist or internist who’s known them [the patient] for 10 years and now they’ve developed a pain problem, you already have a bank of goodwill both ways.” 34 …”
Section: Facilitators Of Prescribing Opioidsmentioning
confidence: 99%